Pengaruh Promosi terhadap Keputusan Pembelian Platform E- Commerce pada Mahasiswa Universitas Patompo - Muh. Yunus; Irham Maulana Yunus (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
This study aims to analyze the effect of promotion on purchasing decisions on the e-commerce platform among FKIP Universitas Patompo students. The research employed a quantitative approach using a questionnaire survey with 60 respondents. Data were analyzed using descriptive statistics and simple regression with the assistance of SPSS. The descriptive results indicate that both promotion and purchasing decisions fall into the medium to high category. The regression equation obtained was Y=5.642+0.766XY = 5.642 + 0.766XY=5.642+0.766X, with a positive regression coefficient of 0.766. The t-test produced a significance value of 0.000 (<0.05), indicating that promotion has a positive and significant effect on purchasing decisions. The correlation coefficient (R) of 0.608 shows a moderately strong positive relationship, while the coefficient of determination (R²) of 0.369 indicates that promotion explains 36.9% of the variation in purchasing decisions, while the remaining 63.1% is influenced by other factors beyond this study. The findings conclude that promotion plays an important role in encouraging students’ purchasing decisions on the e-commerce platform. These results support Kotler and Keller’s theory and are consistent with previous research regarding the importance of digital promotion in consumer behavior.